Comparative Study on Corrosion Resistance Properties of TP2 Phosphorized Copper and Rare Earth Microalloying Pure Copper in HCl Solution - Li, Haihong; Zhao, Qinyi; Wang, Guangzhen; Sun, Xueqin; Zhang, Shangzhou (Asian Journal of Chemistry, 2015)
The mircrostructure, the second phase distribution and the second phase morphology of TP2 phosphorized copper and 0.1 wt. % Ce microalloying pure copper (Cu-0.1Ce) were investigated by optical microscope and scanning electron microscopy. The corrosion properties of TP2 phosphorized copper and Cu-0.1Ce in 0.5 mol/L HCl solution was studied using potentiodynamic polarization tests. The corrosion surfaces were observed by SEM. Results showed that cerium refined the grain sizes and enhanced the corrosion resistance properties of pure copper in 0.5 mol/L HCl solution. The corrosion potential and corrosion current density of TP2 phosphorized copper and Cu-0.1Ce were -193.57 mv, 3.79 × 10-7 A/cm2 and -173.65 mv, 2.06 × 10-6 A/cm2, respectively. At last, the mechanisms of cerium refining grain sizes and improving corrosion resistance properties in acid solution were discussed.